TO THE 150 ANNIVERSARY OF THE BIRTH OF I.V. TROITSKY - G.L. Mikirtichan (Вопросы современной педиатрии, 2006)
The article disclose the important milestones in the life and activities of Ivan Vissarionovich Troitsky (1856–1923), the founder of the pleiad of Russian pediatricians of the second half of the XIX — the beginning of the ХХ centuries. Due to their efforts pediatrics have occupied a proper place among other medical disciplines. The author analyzes principle directions of scientific research and characterize I.V. Troitsky as a public figure and organizer of children's healthcare system. The article emphasis a role that Troitsky played in the calling for the first international and the first all Russian conference of children's doctors (1912).Key words: pediatrics, I.V. Troitsky, scientific problems of pediatrics, principles for therapy in children, conference of children's doctors, «the drop of milk».